2015
DOI: 10.1111/tra.12259
|View full text |Cite
|
Sign up to set email alerts
|

A Second Las17 Monomeric Actin‐Binding Motif Functions in Arp2/3‐Dependent Actin Polymerization During Endocytosis

Abstract: During clathrin-mediated endocytosis (CME), actin assembly provides force to drive vesicle internalization. Members of the Wiskott–Aldrich syndrome protein (WASP) family play a fundamental role stimulating actin assembly. WASP family proteins contain a WH2 motif that binds globular actin (G-actin) and a central-acidic motif that binds the Arp2/3 complex, thus promoting the formation of branched actin filaments. Yeast WASP (Las17) is the strongest of five factors promoting Arp2/3-dependent actin polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…To test that possibility, MATa strains expressing the 319 GFP-tagged proteins in these categories were mated with MATa cells expressing Sla1-RFP from the endogenous locus and resulting diploid cells were selected with appropriate markers. Sla1 is a multifunctional clathrin adaptor and actin polymerization regulator present at all sites of CME and easily visible by fluorescence microscopy ( Figure 1A) (Ayscough et al 1999;Kaksonen et al 2003;Kaksonen et al 2005;Di Pietro et al 2010;Feliciano and Di Pietro 2012;Feliciano et al 2015). Each diploid strain expressing both the corresponding GFP-fusion protein and Sla1-RFP was subjected to live cell confocal fluorescence microscopy and colocalization analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test that possibility, MATa strains expressing the 319 GFP-tagged proteins in these categories were mated with MATa cells expressing Sla1-RFP from the endogenous locus and resulting diploid cells were selected with appropriate markers. Sla1 is a multifunctional clathrin adaptor and actin polymerization regulator present at all sites of CME and easily visible by fluorescence microscopy ( Figure 1A) (Ayscough et al 1999;Kaksonen et al 2003;Kaksonen et al 2005;Di Pietro et al 2010;Feliciano and Di Pietro 2012;Feliciano et al 2015). Each diploid strain expressing both the corresponding GFP-fusion protein and Sla1-RFP was subjected to live cell confocal fluorescence microscopy and colocalization analysis.…”
Section: Resultsmentioning
confidence: 99%
“…GST-and polyhistidine-fusion proteins were expressed in Escherichea coli and purified as described (Feliciano et al 2011(Feliciano et al , 2015. GST-pulldowns were performed by loading glutathioneSepharose beads with GST-fusion protein (5 mg) for 30 min at room temperature.…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…GST-pulldown assays were performed as previously described ( Farrell et al, 2015 ; Feliciano et al, 2015 ). In brief, recombinant polyhistidine-tagged proteins (10 µg) were incubated with GST and GST fusion proteins (10 µg) bound to glutathione-Sepharose beads in 1 ml of PBS containing 0.1% Triton X-100 for 1 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, work from Feliciano et al [23] demonstrated the importance of arginine residue pairs (RR349,350; RR382,383) in Las17 that facilitated G-actin binding within the PPR region. Their study focussed on the role of these residues in the context of Arp2/3 and clearly highlighted the importance of the RR pairs for G-actin binding and for rapid polymerization by Arp2/3.…”
Section: Arp2/3-independent Actin Nucleation By Yeast Las17/wasp Polymentioning
confidence: 99%